Enabling RFID on series 60 mobile phones through Bluetooth connectivity - Peralta, Ann Margaret A.
Bluetooth is a widespread wireless technology commonly used for data transmission in different types of applications. Since most devices nowadays such as cellular phones and PDAs are equipped with Bluetooth, using them as Radio Frequency Identification (RFID) readers would be very much advantageous for numerous applications. The group proposed to implement a system that enables its user to read the contents of a passive RFID tag using a mobile phone that supports Bluetooth and SMS by coupling it with two RFID readers: (1) the SkyeModuleTM M1, which is a high frequency (HF) RFID reader; and (2) the SkyeModuleTM M9, an ultra high frequency (UHF) RFID reader. The RN-24 Class 1 Bluetooth Super Module by Roving Networks is used to transmit the data from either of the RFID readers to the mobile device. The system also includes a remote desktop computer that serves as an external database, and communicates with the mobile phone using a BenQ M23 GSM Module. The information gathered from the passive tag would be automatically forwarded by the mobile device to the computer through SMS messaging. The databse is responsible for storing the information gathered from the RFID tags and updating the status of the products encoded in the system. After an RFID tag is succesfully read, a feedback message is sent to the mobile phone to inform the user about the updates done to the database. The end product of the project is a portable device which works for S60 3rd Edition mobile phones.